Peran Guru Bimbingan Konseling Dalam Meningkatkan Kedisiplinan Dan Tanggung Jawab Siswa SDN 1 Watiginanda - Inang Cahayani; Wa Ode Mareniawati Mustari2; Nengky, Nengky; Riski Andrian Ningsi; Heriawan Rusli Langsang; Haliadi Haliadi (FKIP UNSULTRA, 2026)
This study aims to describe the role of Guidance and Counseling (BK) teachers in improving student discipline and responsibility at SDN 1 Watiginanda. Discipline and responsibility are fundamental character traits that must be instilled from elementary school, as they form the foundation for students' future attitudes and behavior. This study employed a descriptive qualitative approach. The research subjects consisted of BK teachers as primary informants, along with homeroom teachers, principals, and students as supporting informants. Data collection techniques included observation, semi-structured interviews, and documentation. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing, with validity tested through triangulation of sources and techniques. The results indicate that BK teachers play a significant role in improving student discipline and responsibility through classroom guidance services, individual counseling, group counseling, and habituation programs such as class duty, punctuality at school, and adherence to rules. BK teachers also collaborate with homeroom teachers and parents to monitor student behavioral development. The approach used is persuasive, educational, and humanistic, so that students feel comfortable and motivated to improve their behavior. This study concludes that planned, sustainable, and collaborative guidance and counseling services have a positive impact on the development of discipline and responsibility in elementary school students. These findings are expected to serve as a reference for schools in improving the quality of guidance and counseling services as an integral part of character education.